The United Kingdom and United Nations peace operations. Issue 5 (19th October 2016) - Curran, David; Williams, Paul D.
ABSTRACT: This article analyses the United Kingdom's (UK) approach to United Nations (UN) peace operations and whether Britain is prepared politically, bureaucratically, financially, and militarily to increase its contributions to them. The article begins with an overview of UK engagement with UN peacekeeping since 1956 before discussing the political issues that govern British decisions about peacekeeping. The third section then assesses several challenges that would need to be addressed in order for the UK's increased participation in UN missions to be effective. Finally, the article outlines the main factors pushing the UK towards greater engagement with UN peace operations, including opinions voiced by select domestic, international, and institutional audiences.